Study Of Goniothalamin And Bioactive Glass 45s5 (Gtn-bg) On Osteosarcoma (Saos-2) And Breast Adenocarcinoma (Mcf-7) Cells - Bakar, Siti Aishah Abu (2023)
Developing alternative cancer treatment is crucial due to the limitations of conventional chemotherapy, which can harm healthy cells while targeting cancer cells. Plant-derived natural products, with their diverse mechanisms and low toxicity, hold promise as cancer treatments, and their combination with bioactive materials may improve treatment effectiveness. In this study, the cytotoxic activity of a plant styryl-lactone, goniothalamin (GTN) was screened first in several human cancer cell lines and was found to possess a substantial range of cytotoxicity against osteosarcoma (Saos-2), breast adenocarcinoma (MCF-7), breast carcinoma (UACC-732), adenocarcinoma alveolar basal epithelial (A549) and colorectal adenocarcinoma (HT29) cells, but less toxicity towards human bone marrow-derived mesenchymal stem (HMSC) cells. GTN demonstrated selective toxicity towards cancer cells with a high SI value (>2) for each examined cancer cell line compared to doxorubicin (DOX). The potential enhancement of GTN's anticancer effects was explored by combining it with a sol-gel-derived bioactive glass 45S5 (BG 45S5) that possesses bioactive, biocompatible, and biodegradable properties. The combination of GTN-BG was found more potent than GTN in inhibiting the proliferation of Saos-2 and MCF-7 cells due to a better microenvironment provided with the release of ionic dissolution products such as Ca2+, Na+ and Mg2+ ions from the BG. For both GTN and GTN-BG treatments, several apoptotic features were detected when observed under a phase microscope, including cell shrinkage, rounded cells, and membrane blebbing.